2019
DOI: 10.1007/s00702-019-01998-x
|View full text |Cite
|
Sign up to set email alerts
|

Association study and a systematic meta-analysis of the VNTR polymorphism in the 3′-UTR of dopamine transporter gene and attention-deficit hyperactivity disorder

Abstract: Attention-deficit hyperactivity disorder (ADHD) has been postulated to associate with dopaminergic dysfunction, including the dopamine transporter (DAT1). Several meta-analyses showed small but significant association between the 10-repeat allele in the DAT1 gene in 3′-untranslated region variant number tandem repeat polymorphism and child and adolescent ADHD, whereas in adult ADHD the 9-repeat allele was suggested to confer as risk allele. Interestingly, recent evidence indicated that the long-allele variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 114 publications
0
24
0
Order By: Relevance
“…Significant effect of the SLC6A3 genotype showed that subjects with the 9R allele, when compared to those from the 10R group, were characterized by less efficient orienting processes measured with the ANT task and obtained significantly worse results in the TEA-Ch subtests evaluating attentional switching (CL, OA). The association between SLC6A3 10R/10R or 10R/11R genotypes and better performance in cognitive tasks 50 appears counterintuitive, as the 10R allele has been reported as the risk allele for ADHD 51 , and related to poorer performance in cognitive tasks 27,28 . However, the debate on the role of 10R is far from being settled with studies reporting both opposite 29,51 and null 30 effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant effect of the SLC6A3 genotype showed that subjects with the 9R allele, when compared to those from the 10R group, were characterized by less efficient orienting processes measured with the ANT task and obtained significantly worse results in the TEA-Ch subtests evaluating attentional switching (CL, OA). The association between SLC6A3 10R/10R or 10R/11R genotypes and better performance in cognitive tasks 50 appears counterintuitive, as the 10R allele has been reported as the risk allele for ADHD 51 , and related to poorer performance in cognitive tasks 27,28 . However, the debate on the role of 10R is far from being settled with studies reporting both opposite 29,51 and null 30 effects.…”
Section: Discussionmentioning
confidence: 99%
“…The association between SLC6A3 10R/10R or 10R/11R genotypes and better performance in cognitive tasks 50 appears counterintuitive, as the 10R allele has been reported as the risk allele for ADHD 51 , and related to poorer performance in cognitive tasks 27,28 . However, the debate on the role of 10R is far from being settled with studies reporting both opposite 29,51 and null 30 effects. In our study, we did not observe effects of genotype on sustained attention neither in the SART nor for the executive attention assessed with the ANT.…”
Section: Discussionmentioning
confidence: 99%
“…Among the GO biological processes affected by these genes were neurogenesis (GO:0022008; FDR=3.62e −8 ), neuron differentiation (GO:0030182; FDR=2.52e −7 ), and neuron development (GO:0048666; FDR=4.31e −7 ). These processes are potentially related to other findings that have linked VNTRs to neurodegenerative disorders and cognitive abilities (36,39,51,52,53,54,55,56,57,58) (Supplementary material Population specific Go BP.xlsx). The GO term behavior (GO:0007610; FDR=2.22e −4 ) was also found, which could be related to the association of VNTR loci with aggressive behavior (101,102,103).…”
Section: Common Vntr Genotypes Are Correlated With Gene Expression DImentioning
confidence: 61%
“…disease (39,52,53) and Huntington's disease (36,54), and other psychiatric conditions, such as PTSD (55), ADHD (56,57), depression (58), and addiction (59).…”
Section: Introductionmentioning
confidence: 99%
“…Several monoaminergic neurotransmitter circuits have been implicated in ADHD. Notably, genetic studies reveal variants in several genes related to the dopamine system are associated with ADHD, including dopaminergic receptors, enzymes, and transporters [4,5,6,7]. Variants in the dopamine receptor 5 gene ( DRD5 ) modulate age of ADHD onset, while variants in the dopamine transporter ( DAT1 ) gene predict severity of hyperactivity and impulsivity symptoms [8,9].…”
Section: Introductionmentioning
confidence: 99%